BRINE SHRIMP CYTOTOXIC ACTIVITY OF 50% ALCOHOLIC EXTRACT OF CROTON BONPLANDIANUM BAILL. - AJOY, GHOSH; PADMA, CHATTERJEE (Asian Journal of Pharmaceutical and Clinical Research, 2013)
<!–[if gte mso 9]> <![endif]–><span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Objective<span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">: To study the presence of anti-tumorous compounds in Croton bonplandianum. Methods: 50 % ethanolic extract, obtained from dried powdered plant material of C. bonplandianum was assayed for its Brine shrimp cytotoxic activity. Results: It was found that the extract was very effective against brine shrimp and shows LC50 at the concentration of 46.7mg/lit (38 mg/lit -55 mg/lit). Conclusions: It proves the presence of anti-tumorous compounds in C. bonplandianum.<!–[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>